Does Early-Life Misfortune Increase the Likelihood of Psychotropic Medication Use in Later Life?. (July 2018) - Morton, Patricia M.; Ferraro, Kenneth F.
Life-course research has linked childhood experiences to adult mental illness, but most studies focus on anxiety or depressive symptoms, which may be transient. Therefore, this study investigates whether childhood misfortune is associated with taking psychotropic medication, a measure reflecting an underlying chronic mental disorder. Data are from three waves of a national survey of 2, 999 U.S. men and women aged 25–74 years. Four domains of childhood misfortune (childhood socioeconomic status, family structure, child maltreatment, and poor health) are considered—specified as separate domains and a single additive measure—as key predictors of psychotropic medication use. Findings reveal an association between additive childhood misfortune and adult psychotropic medication use, net of adult risk factors. Psychotropic medication use is also more likely during the 20-year study for adults who experienced maltreatment and poor health during childhood. These results reveal the importance of early intervention to reduce consumption of psychotropic medications and associated costs.